Four new triterpenoid saponins isolated from Schefflera kwangsiensis and their inhibitory activities against FBPase1. (March 2016) - Wang, Yan; Liu, Yan-Fei; Zhang, Chun-Lei; Liang, Dong; Luo, Huan; Hao, Zhi-You; Chen, Ruo-Yun; Yu, De-Quan
Graphical abstract: Highlights: Four new triterpenoid saponins, schekwangsiensides H–K were reported. Inhibitory activities against FBPase1 of the triterpenoid saponins were reported. Compounds3, 8, 17, and18 exhibited weak inhibitory activities against FBPase1. Abstract: Four new triterpenoid saponins, schekwangsiensides H–K (1 –4 ) were isolated from the aerial parts of Schefflera kwangsiensis, together with fifteen esters (5 –19 ) of known saponins. The structures of these compounds were elucidated on the basis of spectroscopic data analysis and chemical evidence. Furthermore, in in vitro assays, compounds3, 8, 17, and18 exhibited weak inhibitory activities against fructose-1, 6-bisphosphatase (FBPase1).